Study on Activation Behavior of Complex Fracture Network in Weak-Planar Rock. (9th August 2022) - Chen, Jin; Ran, Lingbo; Zhou, Peiyao; Chen, Wenbin; Tang, Meirong; Wang, Qiang
Abstract : Aiming at the problem of quantifying the composition of complex fracture network and fracture activation after fracturing, a complex fracture network model of weak plane with prefabricated structure is established based on finite element method, global embedded cohesive zone model (CZM), and real shale outcrop. Considering the influence of fully coupled stress/fluid, the effects of weak plane azimuth, horizontal stress difference, fracturing fluid viscosity, and injection rate on fracture network composition, geometry, and stimulated reservoir volume (SRV) are studied. The concept of fracture relative activation rate, which can quantitatively analyze fracture network composition and fracture activation, is proposed. The results show that the fracture geometry of the two kinds of conjugated shale after fracturing is controlled by the most weak mechanical plane, and the fracture network is, respectively, axisymmetric and centrosymmetric. The fracture network is composed of the weak plane fractures with the dominant free gas transport and the matrix microfractures with the dominant adsorbed gas transport. The effects of weak plane azimuth, horizontal stress difference, and fracturing fluid viscosity on SRV length are not monotonous, while the increase of the azimuth, horizontal stress difference, fracturing fluid viscosity, and the reduction of appropriate injection rate will lead to the increase of SRV width. The effect of horizontal stress difference on the relative activation rate of fractures does not change monotonically, while the increase of weak plane azimuth, fracturing fluid viscosity, and injection rate will lead to the increase of the relative activation rate of matrix microfractures, the increase of the total length of activated fractures, and the decrease of the relative activation rate of weak plane fractures.